Ensaios sobre crise e desmedida do capital: notas para uma crítica do subconsumismo - Andrade, Patrick Rodrigues (2011)
This work is structured in two essays on rampant and crisis of capital, and, in the end, some notes as an outline for a critic of underconsumption. The first essay has its central issue the critics elaborated by Rosa Luxemburg to the schemes of social reproduction of Karl Marx, and the interpretation of the author to the meaning of the crisis of capital at the beginning of the 20th century. The first section argues about the theoretical status of the schemes of social reproduction of Marx, the debate surrounding them in the early twentieth century and the analysis undertaken by Rosa Luxemburg in her work The Capital Accumulation (1913). In the second section of this first essay, the analysis focuses on Luxemburg s perspective regarding the crisis of capitalism and her critic of Marx, particularly in terms of a "mismatch" between the schemes of reproduction extended in the second book of Capital and the conception of the capitalist global process of social of the third book. The third section examines some theoretical problems of Luxemburg, presented in earlier sections, under the terms of dialectical logic refined of the notion of "negation of negation", a perspective derived from the Western Marxism, which reaffirms the negative as such. What is questioned is the own conceptual processuality of capital and crisis developed by Karl Marx, a mediation involving the proper relationship between the concept and the non-conceptual. The second essay first discusses the "real abstraction" at the base of the capitalist form of wealth production, which puts dissimilar products in equality and then moves on the sense of the inequality of the same as the distribution rules of surplus-value no longer maintain a direct relationship with the production rules of surplus-value to such an extent that through the transformation of values in prices the value law itself is inverted and the ownership of capital becomes predominant , for how the development of fetishism opens a gap within the capital s profit itself. This essay discusses the commodity fetishism, the fetish of money and finally the capitalist relationship fully reificated in interest-bearing capital, emphasizing, to use a lacanian term, how reality itself has the structure of a fiction. Behind this discussion is the negativity inherent to the capitalist dynamic as a movement of constant resilience and recovery of its contradictions in "higher" levels. The notes, on the end, are limited to comments regarding a current Marxist debate between Michel Husson/Alain Bihr and Francois Chesnais/Louis Gill, however, without great damage, it is possible to extend such considerations, in "old" meaning of "critique of political economy," to the question of the underconsumption within the Marxist tradition, which refers to Rosa Luxemburg (in The Accumulation of Capital), Otto Bauer (in his political testament entitled Between the wars?), Henryk Grossman (in his series of lectures reunited on the volume The law of accumulation and the collapse of the capitalist system), and especially Paul Sweezy (The theory of capitalist development), that marks the end of an intellectual age the "classic tradition" of Marxism